The feasibility of a learner-centered approach in a civil technology classroom - Msimango, Simphiwe Magnificent; Mtshali, Thokozani Isaac (Journal of Education and e-Learning Research, 2025)
Learner-centered approach in Civil Technology remains a critical method to achieve learner outcomes amidst the persistence of polycrisis, such as learner overcrowding. It remains unclear how Civil Technology teachers enact this approach in the face of overcrowding and insufficient hands-on skills learning resources. The purpose of this study is to explore the feasibility of adopting a learner-centered approach within Civil Technology classrooms. Purposive sampling was used to identify seven (7) Civil Technology teachers of different subject specializations to participate in this study. A qualitative research approach and single case study design were adopted. The data collected through semi-structured interviews and open-ended questionnaires were analyzed thematically. The findings revealed that Civil Technology teachers faced challenges in employing a learner-centered approach and preferred group work when conducting practical lessons. Teachers demonstrated cognitive dissonance regarding the use of this approach in large classes, stating it was impossible to attend to each learner’s needs during practical lessons. In fact, the practical lessons (simulations) had been structured such that learners should always work in groups. As a result, this hindered the promotion of a learner-centered approach in Civil Technology classrooms. Therefore, this study recommended that, since teachers have the autonomy to design their own practical lessons, they should consider structuring simulations that can be done individually to foster learner-centeredness. This aligns with the Civil Technology Practical Assessment Task policy, which stresses the need for skilling learners both individually and in groups to achieve satisfactory learner outcomes.